Numerical and Experimental Study on End Effect of Waste-Soil Samples under Uniaxial Compression. (17th March 2022) - Wang, Yukai; Liu, Xiaoli; Pang, Bo
Abstract : In order to investigate the influence of end effect on the waste-soil sample strength under uniaxial compression, the influence law of end effect on the uniaxial compression strength is numerically simulated by the FLAC 3D software, and the reliability of the numerical model is verified by comparing it with the test results. Based on the above model, the influence of end effect on the lateral displacement and stress state of waste-soil samples is simulated, and the formation mechanism of end effect under uniaxial compression is revealed. The results show that, when the friction coefficient increases from 0 to 0.4, the uniaxial compression strength and percentage of triaxial compression units first increase rapidly and then slowly and then finally remain invariant. With the increase of the friction coefficient, the lateral displacement of the sample is significantly reduced. On the end surface, the nearer to the edge one is, the greater the decrease is. The triaxial compression region on the axis section is triangular in distribution; with the increase of the friction coefficient, this region increases first rapidly and then slowly and then finally remains invariant. The end effect produces lateral compression stress by reducing the lateral displacement of the end surface of samples, and lateral compression stress causes the sample to enter the triaxial compression state. With the increase of the friction coefficient, the triaxial compression region increases gradually, and thus, the uniaxial compression strength of the entire sample increases.